2022
DOI: 10.1177/15589447221081864
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Immobilization Mechanisms Have on Radiographic Outcomes and Complication Rates in the Conservative Treatment of Distal Radius Fractures: A Systematic Review

Abstract: Distal radius fractures (DRFs) are among the most common fractures in the United States. Despite their high incidence, there is no consensus on the optimal type of cast or splint to treat these fractures. The purpose of this systematic review is to evaluate the available literature pertaining to the outcomes for different constructs used to conservatively treat DRFs. A literature search of PubMed, Medline, and Embase was conducted to identify research comparing the outcomes of various immobilization mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…However, although this was not a randomized study, it was observed a tendency of the use of short splint/plaster for reducible and stable fractures. 5 - 7 …”
Section: Discussionmentioning
confidence: 99%
“…However, although this was not a randomized study, it was observed a tendency of the use of short splint/plaster for reducible and stable fractures. 5 - 7 …”
Section: Discussionmentioning
confidence: 99%
“…DRFs have a bimodal distribution, with the first peak in the paediatric population and the second peak in the elderly population, in the latter of whom DRFs represent 18% of all fractures [ 2 ]. DRF treatment aims to restore function and minimise complications such as loss of reduction, nerve injury, and pain [ 3 ].…”
Section: Introductionmentioning
confidence: 99%